DNA base excision repair: the Achilles' heel of tumour cells and their microenvironment? - Poletto, M; Legrand, A; Dianov, G (Bentham Science Publishers, 2017)
Our current understanding of cancer suggests that every tumour has individual features. Approaches to cancer treatment require thorough comprehension of the mechanisms triggering genomic instability and protecting cancer cells from therapeutic treatments. Base excision repair (BER) is a frontline DNA repair system that is responsible for maintaining genome integrity. The BER pathway prevents the occurrence of disease, including cancer, by constantly repairing DNA base lesions and DNA single strand breaks caused by endogenous and exogenous mutagens. BER is an important DNA repair system for cancer cell survival, as it can affect both chemoand radio-resistance of tumours. Variations in BER capacity are likely responsible for a number of cases of sporadic cancer and may also modulate cancer sensitivity and resistance to therapeutic treatments. For these reasons, it is broadly accepted that targeting BER enzymes might be a promising approach to personalised anti-cancer therapy. However, recent advances in both treatment strategies and the comprehension of cancer development call for a better understanding of the consequences of BER inhibition. Indeed, the impact on both the tumour microenvironment and healthy tissues is still unclear. This review will summarise the current status of the approaches exploiting BER targeting, describing the most promising small molecule inhibitors and synthetic lethality strategies, as well as potential limitations of these approaches.